Evaluation of Various Pest Management Practices against Shoot and Fruit Borer Leucinodes orbonalis Guenee (Lepidoptera: Crambidae) in Brinjal Solanum melongena L. - Sahoo, B. B.; Jena, M. K.; Mandi, N.; Nayak, B. S.; Moharana, R. L. (International Journal of Bio-resource and Stress Management, 2026)
The experiments were conducted over two consecutive years: from October 30, 2020, to March 30, 2021 (Experiment I), and from December 27, 2021, to May 9, 2022 (Experiment II) at the Regional Research and Technology Transfer Station, Bhawanipatna, Odisha, India. This study aimed to evaluate eight different pest management strategies, comprising of insecticides, Carbofuran 3G, Flubendiamide 39.35SC, Chlorantraniliprole 18.5SC, Emamectin Benzoate 5%SG, Bacillus thuringiensis, Azadirachtin 0.15% EC, Spinosad 45% SG, and Neem cake, against L. orbonalis Among the tested strategies, spraying of Chlorantraniliprole 18.5 SC at 60 g a.i. ha-1 on the 30th, 45th, and 60th days after transplanting (DAT) (T3) was the most effective. It resulted in the highest number of healthy fruits (57.6 fruits plot-1), the lowest number of infested fruits (18.7 fruits plot-1), and the lowest total weight of infested produce (7.6 kg plot-1). The percentage of fruit infestation plot-1 on a weight basis (11.8%) was the lowest, and the percentage reduction of fruit infestation plot-1 on a weight basis (43.3%) was the highest in this practice. The yield (288.0 q ha-1) and percentage of higher yield of S. melongena over the control (27.2%) were the highest in this practice. The benefit-cost ratio (1.7) was the highest in T3. Thus, spraying of Chlorantraniliprole 18.5 SC at 60 g a.i. ha-1 on the 30th, 45th, and 60th DAT serves as the best practice and could be recommended for managing L. orbonalis in S. melongena.